Molecular characterization of antibiotic resistance in Escherichia coli strains from a dairy cattle farm and its surroundings. (15th April 2016) - Navajas‐Benito, Enrique Víctor; Alonso, Carla Andrea; Sanz, Susana; Olarte, Carmen; Martínez‐Olarte, Roberto; Hidalgo‐Sanz, Sara; Somalo, Sergio; Torres, Carmen
Abstract: BACKGROUND: This study describes the phenotypic and genotypic characteristics of 78 genetically different Escherichia coli recovered from air and exudate samples of a dairy cattle farm and its surroundings in Spain, in order to gain insight into the flow of antimicrobial resistance through the environment and food supply. RESULTS: Antimicrobial resistance was detected in 21.8% of the 78 E. coli isolates analyzed (resistance for at least one of the 14 agents tested). The highest resistance rates were recorded for ampicillin, nalidixic acid, trimethoprim/sulfamethoxazole and tetracycline. The resistance genes detected were as follows (antibiotic (number of resistant strains), gene (number of strains)): ampicillin (9), bla TEM‐1 (6); tetracycline (15), tet (A) (7), tet (B) (4), tet (A) + tet(B) (1); chloramphenicol (5), cmlA (2), floR (2); trimethoprim/sulfamethoxazole (10), sul2 (4), sul1 (3), sul3 (2), sul1 + sul2 (1); gentamicin‐tobramycin (1), ant (2″) (1). About 14% of strains showed a multidrug‐resistant phenotype and, of them, seven strains carried class 1 integrons containing predominantly the dfrA1‐aadA1 array. One multidrug‐resistant strain was found in both inside and outside air, suggesting that the airborne spread of multidrug‐resistant bacteria from the animal housing facilities to the surroundings is feasible. CONCLUSIONS: This study gives a genetic background of the antimicrobial resistance problem in a dairy cattle farm and shows that air can act as a source for dissemination of antimicrobial‐resistant bacteria. © 2016 Society of Chemical Industry